Social identity and its relationship to mental health among students of the University of Charmu - Reboar Mohammed Amin Qader (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
This research indicated the relation between statistical indication and meaning of social identity the students at Charmu University of Kurdistan Region between (2017- 2018). The research program described the reasons and phenomenon’s which are the study include of it. Furthermore, this research is a practical study among the students at charmu University. Research population in this took part at at students, males and females divided in Jamjamal university, faculty of education that included 1, 2,3,4, stages of students, Morning class; as they were (1246) persons, of whom (424) are male and (822) are female. Research sample seems to be randomly class and applied of charmu University which contained (268) students from both males and females. So, the social identity measurement realization, which was prepared for the research was used. which therefore consists of (44) clauses and the meaning of statistical indication from (Salim, 2006), I have as well, used (45) clauses, as to resolve statistical data, and also the researcher used SPSS because is suitable with the Research aim. Lastly, the aim of this study indicated a significant relation between meaning of life and Achieving identity among the students at Sulaimani University. On the light of the outcomes of the study, the Researcher concluded at the recommendations and proposals relevant to the nature of the results of the study.